Analysis of Soil Response during High-Frequency Vibratory Steel Pipe Pile Driving in Soft Soil - Fengjun Chen; Xiaomi Li; Huiling Zhao; Pei Hu (Advances in Civil Engineering)
High-frequency vibratory pile driving exhibits remarkable efficiency in soft soil, with its impact on the surrounding soil to a limited range. Studying the evolution of stress and strain fields in the soil surrounding the pile during the pile driving process is of great significance for effective control of pile driving construction and accurate prediction of the pile foundation’s bearing capacity after installation. In this study, by means of numerical simulation with consideration of the large deformations of the soil and even discontinuities induced by the pile penetration into soil, the response of the soil during the high-frequency vibratory steel pipe pile driving in silt soil was investigated. The research results show that with the increase of pile driving depth, the stress concentration zones in the soil near the pile tip continuously expanded, and the plastic strain zone mainly developed downward but little horizontally. When the vibration frequency was between 33 and 38 Hz, the pile driving efficiency was higher than that of 50 Hz. High-frequency resonance free vibratory pile driving has smaller pile–soil stresses and plastic strains compared to traditional impacting pile and static pile, and it is less prone to the formation of soil plug. Therefore, high-frequency vibratory pile driving technology exhibits good adaptability in the soft soil.